Gastro-Protective and Therapeutic Effect of Punica granatum against Stomach Ulcer Caused by Helicobacter Pylori: Effect of Punica granatum against Stomach Ulcer - Muhialdin, Ali J.; Alamri, Zaenah Zuhair; M. Hussein, Ali; Faraj, Rahman K.; Taha, Zhala B.; Hussein, Mohammed M.; Mojarradgandoukmolla, Shahrokh (Cellular and Molecular Biology, 2023)
Gastric ulcer is a chronic condition that occurs when the mucosa of the stomach is broken. There is a physiological equilibrium between aggressive factors and mucosal defense. The purpose of this research was to compare the prevention level and efficiency of herbal medicinal plants (Punica granatum) to the omeprazole drug. Many groups were prepared from Albino male rats, the first control group (inoculate with H. pylori and fed with standard pellet), the Second group, rats inoculated by H. pylori and prevented with Punica granatum aqueous extracts (PGAE) in two dosages (250mg/kg, 500mg/kg), and last group inoculated by H. pylori and prevented with standard drug omeprazole at the dose (20mg/kg). The results showed that the Ulcer Inhibition % of Punica granatum with a high dose of 500mg/kg and a low dose of 250mg/kg was 84.60±5.48 and 42.87±7.14, respectively. While in the omeprazole treatment group, Ulcer Inhibition % was 24.50±6.35 and this Ulcer Inhibition % in the Punica granatum treatment groups was significant compared to the omeprazole treatment group and the control group (P=0.0001). PGAE displayed a significant lessening in stomach index and infectious cell proliferation with much cell damage. Although the result of the current study improves, a high dosage of aqueous extracts of plants has more effectiveness than a low dosage of aqueous extracts plants.